The Evaluation of the Containment Efficacy of Semi-Rigid Isolators for Housing Cages of Laboratory Animals Infected With BSL-3 Agents. (23rd June 2021) - DeTolla, Louis; Johnson, David K; Reynolds, Scott D; Sanchez, Rigoberto; Weichbrod, Robert H; Terzi, Matthew C
Abstract: Research animals models infected with Biosafety Level-3 (BSL-3) agents need to be housed in specialized biocontainment caging. Most of these specialized cages have input and exhaust that is high efficiency particulate air filtered and sealed to prevent escape of the BSL-3 agent. An alternative to the use of the above BSL-3 biocontainment caging is the use of a flexible film or modified semi-rigid plastic film isolator that has its own high efficiency particulate air–filtered input and exhaust and is sealed with respect to the animal room environment, thus preventing BSL-3 agent escape. Standard caging can be housed within such an isolator. Computational fluid dynamics was used to evaluate the integrity of modified semi-rigid isolators for containment of aerosolized BSL-3 agents. Three isolators were located inside an animal BSL-3 room to provide an extra tier of protection and to permit different infectious studies within the same room while reducing or eliminating the risk of cross-contamination. The isolators were sized to house caging for rabbits and smaller non-human primates such as marmosets, African greens, and macaques. Multiple case studies of failure scenarios were investigated, including isolator breaches through the plastic membrane seam separation and rips, and exhaust fan failure. Breaching the level of containment provided by the isolators required the improbable simultaneous event of a plastic membrane rip in addition to the rare malfunction of the back-up exhaust fans. Each isolator was equipped with 2 blower motors connected in parallel to a common exhaust plenum and a battery backup. Even with this rare double (simultaneous) event, the animal BSL-3 room air exhaust system was able to contain the few droplets released in the simulated computational fluid dynamics breach. The modified semi-rigid isolators with negative airflow proved safe and effective for aerosol studies using BSL-3 agents, even in the unlikely event of a breach in containment.